Modelling dependence in cointegrated data Copula-based cointegrated vector autoregressive models - Taima, Hideaki (Quezon City University of the Philippines, 2008)
The copula method is well applied in finance and actuarial science but its application in economic studies is limited and its use in the cointegration framework virtually nil. This paper explores the use of copula method to analyze the remaining dependence after a cointegration relationship is modeled. Specifically, simulated data is used to characterize the behavior of the dependence parameter of several copulae fitted to the distribution of the residuals after cointegrated VAR and VECM models are fitted. The Clayton copula, Frank copula, Gaussian copula, Gumbel copula and Plackett copula are used. The density forecasting ability of the copula-basaed VAR and VECM is then compared with that of standard models via conditional KLIC divergence measure using stimulated data. The consumption-income relationship in Japan is then modeled with copulae and the variousm models are evaluated using Hansen's SPA test. The results reveal that the copula-based models generally show better density forecasting ability compared with standard models in both simulated data and empirical data.
Thesis ( M.S.) --University of the Philippines